La industria lítica bifacial del sitio en cantera Chipana-1 : conocimiento y técnica de los grupos humanos del Desierto de Atacama, norte de Chile al final del Pleistoceno - Herrera, Katherine A. (BAR international series. Paris monographs in American archaeology, 2018)
The site of Chipana-1 is located in the middle of the Atacama Desert, in the Pampa del Tamarugal. The site is a good example of past societies adaptation to hyper-arid environments, and provides new insights into the early human occupations of South America. The well-preserved stratigraphic record, together with 13 radiocarbon dates, show that the site was occupied around 11,480 cal BP. Chipana-1 is a lithic raw-material extraction and workshop site, of a silicified rock of good quality, mainly related to the production of bifacial tools (façonnage), and to a lesser extent, of flakes (débitage) on surface. This is the first site in northern Chile that provides information on the first stages of lithic production, such as raw-material selection and reduction (dégrossissage).